Bedtime Stories and the Development of Language Skills in Early Childhood - Isah Cahyani; Siti Amila Rafiani Silmi; Siti Arina Hasanah (Early Childhood Education & Parenting, 2025)
Traditional games play a vital role in developing children's motor skills, particularly in a family environment. This article examines the influence of traditional games on gross and fine motor skill development through a qualitative approach combining literature review and family case studies. Traditional games such as jump rope, congklak, and egrang enhance coordination, balance, strength, and agility in children. Observations reveal that children engaged in these games demonstrate better motor development than those who are not. Parental involvement in traditional games strengthens family bonds, provides a supportive environment, and enhances children's social skills. The article concludes by emphasizing the importance of integrating traditional games into children's daily routines to promote motor skill development and encourages further research on their broader impact on child development.